Modul Belajar Elektronik pada Materi Ajar Merakit Personal Computer - Putra, Ranggri Pratama R; Supraptono, Eko; Wibowo, Hendro (Jurusan Teknik Elektro Universitas Negeri Semarang, 2016)
The purpose of this study was to develop an electronic learning modules that can be used to support learning assemble a personal computer (PC) as well as implement the electronic learning modules in order to increase interest and student learning outcomes. The method used in the study is the Research and Development (R & D) research design one-group pretest-posttest. The steps in the research include analysis of the potential and problems, data collection, product design, design validation to the expert media and materials, design revision, the revision of the product as well as product testing to students of class X TKJ SMK Islam Sudirman II Ambarawa. Media developed feasible for use as a learning support assemble a personal computer (PC) based on the results of the validation. The results of hypothesis testing using t-test showed that the value t table = 2.045 <t = 4.67 which means Ha accepted and the average yield learn to assemble personal computer (PC) using an electronic learning module is greater than 80. By testing n- the gain obtained by the gain of 0.44, or 44%, which is within the range of 0.3 <g <0.7 were categorized as moderate, it can be said has increased significantly. Results of student questionnaire responses to aspects of feeling happy, student interest, attention, and aspects of the involvement of students showed a very positive response.